Aplikasi Pembelajaran Doa Dan Tajwid Pada Madrasah Ibtidaiyah Swasta Sholihin Di Tanjung Morawa, Sumatera Utara - Liza Fitriana; David; Sarudin (Universitas Harapan Medan, 2025)
This study aims to develop a desktop-based digital learning media for daily prayers and tajwid for students of Madrasah Ibtidaiyah Swasta Sholihin in Tanjung Morawa, North Sumatra. The research is motivated by the low learning motivation and difficulties of ele-mentary-level students in understanding tajwid rules and memorizing daily prayers when learning is still dominated by conventional lecture methods and static textbooks. The method used is Research and Development, employing a model that includes needs analy-sis, user interface design, program coding using Visual Basic, and expert validation by material and media specialists. The resulting product is a learning application in .exe format with two main menus, namely the Prayer Menu containing 20 daily prayers and the Tajwid Menu containing basic tajwid rules, each equipped with Arabic text, Latin transliteration, translation, illustrations, and clear audio pronunciation to support the Tahsin method and independent memorization. Validation results show that the content complies with reli-gious principles, the application navigation runs properly, and the visual appearance is con-sidered attractive, thereby increasing student enthusiasm and engagement. Classroom im-plementation indicates that the use of this application creates a more dynamic and interac-tive learning atmosphere, helps improve the quality of Quran recitation, and accelerates the memorization of daily prayers compared to conventional teaching methods